A global RNA‐seq‐driven analysis of CHO host and production cell lines reveals distinct differential expression patterns of genes contributing to recombinant antibody glycosylation. Issue 9 (26th August 2015) - Könitzer, Jennifer D.; Müller, Markus M.; Leparc, Germán; Pauers, Martin; Bechmann, Jan; Schulz, Patrick; Schaub, Jochen; Enenkel, Barbara; Hildebrandt, Tobias; Hampel, Martin; Tolstrup, Anne B.
Abstract Boehringer Ingelheim uses two CHO‐DG44 lines for manufacturing biotherapeutics, BI‐HEX‐1 and BI‐HEX‐2, which produce distinct cell type‐specific antibody glycosylation patterns. A recently established CHO‐K1 descended host, BI‐HEX‐K1, generates antibodies with glycosylation profiles differing from CHO‐DG44. Manufacturing process development is significantly influenced by these unique profiles. To investigate the underlying glycosylation related gene expression, we leveraged our CHO host and production cell RNA‐seqtranscriptomics and product quality database together with the CHO‐K1 genome. We observed that each BI‐HEX host and antibody producing cell line has a unique gene expression fingerprint. CHO‐DG44 cells only transcribe Fut10, Gfpt2 and ST8Sia6 when expressing antibodies. BI‐HEX‐K1 cells express ST8Sia6 at host cell level. We detected a link between BI‐HEX‐1/BI‐HEX‐2 antibody galactosylation and mannosylation and the gene expression of the B4galt gene family and genes controlling mannose processing. Furthermore, we found major differences between the CHO‐DG44 and CHO‐K1 lineages in the expression of sialyl transferases and enzymes synthesizing sialic acid precursors, providing a rationale for the lack of immunogenic NeuGc/NGNA synthesis in CHO. Our study highlights the value of systems biotechnology to understand glycoprotein synthesis and product glycoprofiles. Such data improve future production clone selection and process development strategies for better steering of biotherapeutic product quality.